THE EFFECT OF COMPENSATION AND CAREER EVELOPMENT THROUGH SCIENTIFIC PUBLICATION MOTIVATION ON THE PERFORMANCE OF HOMEBASE ISLAMIC EDUCATION LECTURERS AT THE UNIVERSITY - Ali Imron; Robingun Suyud El Syam (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2023)
The research aims to determine the effect of compensation and career development through motivation on performance. This study used a proportionate stratified random sampling technique, with a total of 27 samples distributed to Lecturers of Islamic Religious Education at the University of Science Al-Qur'an Wonosobo. The research analysis used Structural Equation Modeling (SEM) with the LISREL program. The results of the study stated that when career development was increased, the motivation of the PAI lecturer at the Al-Qur'an Science University of Wonosobo also increased. When compensation is done well, the motivation of the lecturers increases. When lecturers have high work motivation, their performance is also high. When career development is increased, performance increases. When the process of giving compensation is done well, performance increases. When the career development process is improved through motivation, the performance of the lecturers increases. When compensation is increased through motivation, the performance of lecturers increases. This research provides advice to the leaders of the University of Al-Qur'an Science Wonosobo so that the provision of compensation and the career development process for lecturers is improved.